PENGARUH SELF ESTEEM TERHADAP KECANDUAN INTERNET PADA GEN Z - Nurulsani S Abd Latief (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2026)
Generation Z has grown alongside the development of information technology, with the internet serving as a primary medium for information, communication, and identity formation. This study aims to examine the effect of self-esteem on internet addiction among Generation Z. The research employed a quantitative descriptive correlational approach with data collected through online questionnaires. The study population consisted of 350 Generation Z individuals in North Maluku Province, with a sample of 216 respondents selected using purposive sampling based on the criteria of being aged 14–28 years and using the internet for more than 6 hours per day. The research instruments demonstrated high reliability, with Cronbach’s Alpha values of 0.969 for the self-esteem scale and 0.942 for the internet addiction scale, each consisting of 20 items. Simple regression analysis revealed that self-esteem had a significant effect on internet addiction with a significance value of 0.001 (p < 0.05), and the Pearson correlation coefficient of 0.237 indicated a positive relationship between the two variables.